2017
DOI: 10.1371/journal.ppat.1006413
|View full text |Cite
|
Sign up to set email alerts
|

Genomic fossils reveal adaptation of non-autonomous pararetroviruses driven by concerted evolution of noncoding regulatory sequences

Abstract: The interplay of different virus species in a host cell after infection can affect the adaptation of each virus. Endogenous viral elements, such as endogenous pararetroviruses (PRVs), have arisen from vertical inheritance of viral sequences integrated into host germline genomes. As viral genomic fossils, these sequences can thus serve as valuable paleogenomic data to study the long-term evolutionary dynamics of virus–virus interactions, but they have rarely been applied for this purpose. All extant PRVs have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…While the replication of Caulimoviridae does not require integration into host genomes, endogenous plant pararetroviruses (EPRVs) were identified in many angiosperms in the pregenomic era (17), for example, banana (18) and tobacco (19). Genome-scale data provide important resources to explore the distribution and diversity of EPRVs within plant genomes, which would improve our understanding of the macroevolution of Caulimoviridae and the relationship between viruses and their hosts (20). By mining a variety of plant genomes, Geering et al (21) identified a novel lineage of EPRVs in flowering plants (angiosperms), sometimes with a high copy number, which was designated "Florendovirus" and was thought to constitute a new genus within the Caulimoviridae.…”
mentioning
confidence: 99%
“…While the replication of Caulimoviridae does not require integration into host genomes, endogenous plant pararetroviruses (EPRVs) were identified in many angiosperms in the pregenomic era (17), for example, banana (18) and tobacco (19). Genome-scale data provide important resources to explore the distribution and diversity of EPRVs within plant genomes, which would improve our understanding of the macroevolution of Caulimoviridae and the relationship between viruses and their hosts (20). By mining a variety of plant genomes, Geering et al (21) identified a novel lineage of EPRVs in flowering plants (angiosperms), sometimes with a high copy number, which was designated "Florendovirus" and was thought to constitute a new genus within the Caulimoviridae.…”
mentioning
confidence: 99%
“…EPRVs in hosts record past viral infections [11] and have coevolved with their hosts, providing an opportunity to study the evolutionary correlation between viruses and hosts [14]. In the current study, the coevolution of bananas and BSVs in China was investigated (Figure 7) by analyzing the BEVs gene characteristics, BEVs distribution in different banana chromosomes, and the various cultivated bananas, together with the findings of previous research [9,20], to reveal the coevolutionary relationship between BSVs and bananas.…”
Section: Coevolution Of Bevs With Bsvs and Bananasmentioning
confidence: 93%
“…EPRVs, as viral fossils, play a critical role in gene transfer from virus to host [11]. They have become an essential component of the genomes of host plants with time [31].…”
Section: Bevs In Different Genotypes Of Bananasmentioning
confidence: 99%
See 1 more Smart Citation
“…The mining and analysis of EVEs has had an important impact on the emerging field of paleovirology, with implications for the characterization of viral origins and evolution as well as host–virus and virus–virus coevolution ( Patel et al. 2011 ; Feschotte and Gilbert 2012 ; Aiewsakun and Katzourakis 2015a ; Chen et al. 2017 ).…”
Section: Introductionmentioning
confidence: 99%